Madrid, Biblioteca Nacional Mss/4683: il codice e i suoi scoliasti - Caballero-Sánchez, Paula María (Medioevo Greco 13 (2013). Edizioni dell'Orso, pp.1-10., 2013)
Among the preserved Aristophanes’ codices veteres, there is the Madrid, Biblioteca Nacional Mss/4683, an important manuscript for its paleographical and philological value which shows how Aristophanes was read and commented in Byzantium, especially during the Palaeologan period (1261-1453). The current paper deals with the textual and paleographical study of the main scribe and the marginal hands that wrote scholia on the comedies, to find out the exegetical tradition of the manuscript.
Keywords: Aristófanes; Codicología; Aristophanes; Codicology; Byzantine Studies; Textual Transmission; Byzantine Scholarship and Education; Byzantine philology